Assessing future local sea level rise in the islands of the outermost regions of the European Union - Pablo FRAILE-JURADO (European Journal of Geography)
The aim of this paper is to develop a methodology to calculate the sea level rise (SLR) caused by global warming in the Outermost Regions (ORs) of the European Union, mostly represented by islands. ORs are especially vulnerable to SLR since their economies are based mostly on coastal activities. There is a lack of studies at local scale about this phenomenon, mainly caused by the data requirements of the statistical methods used to predict future SLR. Long-term series of tide gauges located on ORs often do not meet the needs of these methods. Therefore, in this paper we proposed a methodology based on the comparison between observed local (from tide gauges of ORs) and global SLR time series. It allows to estimate SLR from short or incomplete time series for future scenarios in ORs SLR. In general, the results show that most of the ORs will suffer from a significant SLR. The differences between the predicted SLR and the expected sea level rise according to future scenarios are not minor.